2007
DOI: 10.4103/0028-3886.35683
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal meningitis: Clinical, diagnostic and therapeutic overviews

Abstract: Cryptococcal meningitis has emerged as a leading cause of infectious morbidity and mortality in patients with AIDS. Among the human immunodeficiency virus (HIV)-seropositive subjects, cryptococcal meningitis is the second most common cause of opportunistic neuro-infection. Current trends are changing due to the marked improvement of quality and length of life produced by highly active antiretroviral therapy (HAART). The introduction of generic HAART in India has resulted in an increase in the number of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 28 publications
2
51
1
6
Order By: Relevance
“…In most studies, headache is considered the predominant clinical manifestation 4,30 . Similar to the results of Aslan and Chandrasekhara, in the present study, headache was the most common symptom observed, and altered sensorium was determined to be the poorest prognostic factor 30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In most studies, headache is considered the predominant clinical manifestation 4,30 . Similar to the results of Aslan and Chandrasekhara, in the present study, headache was the most common symptom observed, and altered sensorium was determined to be the poorest prognostic factor 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Species identifi cation was determined using L-canavanine-glycine-bromothymol blue (CGB) medium to distinguish between C. neoformans and C. gattii isolates 10 . Molecular analysis was conducted using oligonucleotides of the minisatellite-specifi c sequence of phage M13 and of the microsatellite-specifi c sequence (GACA) 4 11,12 . Written informed consent was obtained from each patient.…”
Section: Microbiologymentioning
confidence: 99%
See 2 more Smart Citations
“…are important fungal pathogens worldwide. Cryptococcal meningitis is the fourth most common life-threatening opportunistic infection in individuals with AIDS [1], but is rare among immunocompetent hosts [2,5]. Cryptococcosis is a systemic mycosis associated with significant morbidity and mortality [3].…”
Section: Introductionmentioning
confidence: 99%